2018
DOI: 10.1111/apm.12813
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Ebp pili among clinical and fecal isolates of Enterococcus faecalis and evaluation for human platelet activation

Abstract: Although Enterococcus faecalis is known as normal flora in colon, it is also amongst the most common causative agents of infective endocarditis (IE). Platelet activation resulting from adherence to platelets is an essential step in the pathogenesis of IE. One of the factors proposed in adhesion is endocarditis- and biofilm- associated pili encoded by ebp operon. The aim of this study was to investigate ebp in isolates from different origins and analyze the potential of isolates to activate human platelets of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Moreover, the Enterococcus faecalis was shown to be enriched in severe/critical COVID-19, which was related to enhanced expression of genes related to platelet aggregation and neutrophil degranulation. Previous studies demonstrated that some clinical isolates of Enterococcus faecalis could cause aggregation of human platelets [38] or activate human platelets in vitro [39], while sonicated extract of Enterococcus faecalis could suppress the cell cycle transition and inhibit lymphocytes response [40]. Hence, we assume that the observed dysregulation of certain gut microbes might not be a passenger but a potential driver for the severity of COVID-19.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, the Enterococcus faecalis was shown to be enriched in severe/critical COVID-19, which was related to enhanced expression of genes related to platelet aggregation and neutrophil degranulation. Previous studies demonstrated that some clinical isolates of Enterococcus faecalis could cause aggregation of human platelets [38] or activate human platelets in vitro [39], while sonicated extract of Enterococcus faecalis could suppress the cell cycle transition and inhibit lymphocytes response [40]. Hence, we assume that the observed dysregulation of certain gut microbes might not be a passenger but a potential driver for the severity of COVID-19.…”
Section: Discussionmentioning
confidence: 87%
“…Specifically, Enterococcus faecium is found to be enriched in severe COVID-19 cases, which is linked to heightened expression of genes associated with platelet aggregation and neutrophil-granulocyte degranulation ( 38 ). Prior research has demonstrated that certain clinical isolated strains of Enterococcus faecium possess the ability to induce human platelet aggregation ( 39 ) or activate human platelets in vitro ( 40 ). Additionally, the ultrasonic extract derived from Enterococcus faecium has been found to impede cell cycle progression and suppress lymphocyte response ( 41 ).…”
Section: Discussionmentioning
confidence: 99%